2006
DOI: 10.1063/1.2171513
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic, electrical, and magnetic properties of the system La0.7Sr0.3Mn1−xFexO3

Abstract: On the basis of x-ray structural data and studies of the electrical, magnetic, and magnetoresistive properties and the ferromagnet resonance spectra of ceramic samples of La0.7Sr0.3Mn1−xFexO3 (0⩽x⩽0.10) it is established that a competition between structural changes influencing the ferromagnetism leads to a monotonic weakening of the ferromagnetism (a lowering of TC by around 5K∕%Fe). The increase of the magnetoresistance in the low-temperature region and the large values of the low-field contribution to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
1
6
0
2
Order By: Relevance
“…Investigations of LSMFO have revealed a high sensitivity of magnetic and transport properties to Fe doping [16][17][18][19][20]. In particular, it has been established a strong decrease of the FM Curie temperature, T C , with y, attributable to two different reasons [20].…”
Section: Introductionmentioning
confidence: 98%
“…Investigations of LSMFO have revealed a high sensitivity of magnetic and transport properties to Fe doping [16][17][18][19][20]. In particular, it has been established a strong decrease of the FM Curie temperature, T C , with y, attributable to two different reasons [20].…”
Section: Introductionmentioning
confidence: 98%
“…1b). With increasing iron content the shape of FMR spectra does not change considerably over a wide concentration range, 11 which corresponds to the dopant concentration limits for the model X (see Table 1). …”
Section: Resultsmentioning
confidence: 93%
“…Ferromagnetic order in substituted manganites originates from the so-called double exchange interaction between Mn ions which are in different oxidation states (Mn 3+ and Mn 4+ ) [20]. Earlier, it was shown that Fe ions do not take part in the double exchange [12,13,21]. As a result, Fe substitution for Mn simply reduces the number of Mn ions participating in the double exchange.…”
Section: Resultsmentioning
confidence: 99%